Depressive disorder, coronary heart disease, and stroke: dose–response and reverse causation effects in the Whitehall II cohort study. (29th August 2020) - Brunner, Eric J; Shipley, Martin J; Britton, Annie R; Stansfeld, Stephen A; Heuschmann, Peter U; Rudd, Anthony G; Wolfe, Charles DA; Singh-Manoux, Archana; Kivimaki, Mika
Abstract: Background: Systematic reviews examining associations of depressive disorder with coronary heart disease and stroke produce mixed results. Failure to consider reverse causation and dose–response patterns may have caused inconsistencies in evidence. Design: This prospective cohort study on depressive disorder, coronary heart disease, and stroke analysed reverse causation and dose–response effects using four 5-year and three 10-year observation cycles (total follow up 24 years) based on multiple repeat measures of exposure. Methods: Participants in the Whitehall II study ( n = 10, 036, 31, 395 person-observations, age at start 44.4 years) provided up to six repeat measures of depressive symptoms via the 30-item General Health Questionnaire (GHQ-30) and one measure via Center for Epidemiologic Studies Depression Scale (CES-D). The cohort was followed up for major coronary events (coronary death/nonfatal myocardial infarction) and stroke (stroke death/morbidity) through the national mortality register Hospital Episode Statistics, ECG-screening, medical records, and self-report questionnaires. Results: GHQ-30 caseness predicted stroke over 0–5 years (age-, sex- and ethnicity-adjusted HR 1.60, 95% CI 1.1–2.3) but not over 5–10 years (HR 0.94, 95% CI 0.6–1.4). Using the last 5-year observation cycle, cumulative GHQ-30 caseness was associated with incident coronary heart disease in a dose–response manner (1–2 times a case: HR 1.12, 95% CI 0.7–1.7; 3–4 times: HR 2.06, 95% CI 1.2–3.7), and CES-D caseness predicted coronary heart disease (HR 1.81, 95% CI 1.1–3.1). Conclusions: There was evidence of a dose–response effect of depressive symptoms on risk of coronary heart disease. In contrast, prospective associations of depressive symptoms with stroke appeared to arise wholly or partly through reverse causation.